The degree of including twenty-first century skills in the developed seventh grade mathematics textbook in Jordan - Bahjat Altakhayneh (Umm Al-Qura University, 2022)
This study aimed to investigate the degree of including twenty-first century skills in the developed mathematics textbooks of seventh grade students in Jordan for the 2021/2022 academic year, and the degree to which these skills are distributed in mathematics textbooks for seventh grade students. The study sample consisted of exercises, examples and problems contained in the prescribed mathematics books, and the training, example, or problem was chosen as a unit of analysis, and its number was (1717), and it was classified in light of the skills of the twenty-first century: critical thinking and problem solving, creative thinking, communication, employing technology, Self-learning, collaboration and community participation. The results of the study showed that mathematics textbooks for seventh grade students included the twenty-first century skills with an average percentage of (43%) of all skills, and the skills were ranked in descending order as follows: critical thinking and problem solving (21%), self-learning (7%), creative thinking (6%), communication (6%), employing technology (2%), cooperation and community participation (1%).